REPRESENTASI BRAND IDENTITY TOYOTA DALAM WEBSERIES MENGAKHIRI CINTA DALAM 3 EPISODE SEBAGAI MEDIA PEMASARAN - Afra Dhea Kinandani; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT In this modern days, Internet has melted into a part of society. The significant role of internet in the business world helped change the marketing concept done by companies. The Toyota brand as a famous Japanese automotive brand, act as a sponsor for the production of “Mengakhiri Cinta Dalam 3 Episode” web series by Cerita Films. The promotion for a new variant of Yaris manufactured by Toyota called New Yaris, is the expected outcome why Web Series is chosen as the media of promotion. Yaris is universally known as a nimbler version of vehicle manufactured by Toyota, portrayed as a vehicle owned by youngsters lived in the urban area. The slender design is created with the intention to adapt into the cramped and full-of-traffic urban area. The purpose of this research is to determine the symbol, index, and sign used as representation of Toyota’s brand identity shown in “Mengakhiri Cinta dalam 3 Episode” webseries. This study uses a qualitative research method of literature by analyzing web series and comparing with journals or other similar research. Data collection techniques consist of observation and literature study. While the data analysis technique used semiotic analysis of Charles Sanders Pierce. The results of this study show that Toyota in Brand as Product is represented by a sign or representation based on what is shown directly in this web series which has 4 episodes (audio and visual captured by the audience's five senses), where this film uses a lot of long shots and close ups. ; Brand as Organization is represented by organizational attributes, indicated by displaying the superior features of the Toyota New Yaris; Brand as is represented by the object through the New Yaris car used by Satrio which is bright yellow and several other Toyota cars which are the black or silver background; Brand as Symbol is represented by the interpreter through the characters that are brought and built in Satrio and Ayu, representing the work of urban youth and their characters who want to be fast and comfortable. Keywords: brand identity, promotion, representation, webseries